Multisystem Inflammatory Syndrome in Children (MIS-C)—A Case Series in December 2020 in Vienna, Austria - Kurz, Herbert; Gombala, Tomas (Frontiers in Pediatrics, 2021)
MIS-C is a novel clinical syndrome in children and adolescents, was first encountered in the spring of 2020 as a post COVID-19 multisystem inflammatory syndrome. The highest number of SARS-CoV-2 infections in Austria were registered in November 2020. In December 2020, eight patients with MIS-C were hospitalized at the pediatric department of Klinik Donaustadt, a large municipal hospital in Vienna. Six of the patients needed pediatric intensive care. As we lack any international consensus on the diagnosis and treatment of this severe complication, we used a multidisciplinary approach. The purpose was to establish an internal standard for maximizing the efficacy and safety of treatment, and standardizing the clinical management of this disease.